2019
DOI: 10.7567/1347-4065/aaf4b6
|View full text |Cite
|
Sign up to set email alerts
|

Study on fabrication of conductive antimony doped tin oxide thin films (SnOx:Sb) by 3rd generation mist chemical vapor deposition

Abstract: Transparent conducing antimony doped tin oxide (SnOx:Sb) thin films were fabricated by solution-processed atmospheric-pressure 3rd generation mist chemical vapor deposition (3rd G mist CVD) system with two solution chambers and one mixing chamber to control the atmosphere in reaction area. To study how to reduce the resistivity, the effects of each additive component in dopant solution were investigated; this was followed by identification of components contributing to the fabrication of SnOx:Sb films. Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Crystallite size is associated with electrical properties. Lopez-Maldonado et al reported that increasing crystallite size decreases the grain boundaries, decreasing the energy barrier width, which influences the electrical conduction properties 35 . There is no significant difference in FWHM for other diffraction planes.…”
Section: Structural Analysismentioning
confidence: 99%
“…Crystallite size is associated with electrical properties. Lopez-Maldonado et al reported that increasing crystallite size decreases the grain boundaries, decreasing the energy barrier width, which influences the electrical conduction properties 35 . There is no significant difference in FWHM for other diffraction planes.…”
Section: Structural Analysismentioning
confidence: 99%
“…This precious control of mist ow, which makes mist CVD different from spray and AACVD techniques, is achieved by the following physics: the existence of Leidenfrost state droplets (ELSD) and the low probability of collisions between mist droplets (LPCD). [14][15][16][17][18] As reported in some of the literature, the 2 nd and 3 rd generation mist CVD has been used to fabricate several metal oxide lms. [19][20][21][22][23] Moreover, in contrast to previous research, which improved the lm conductivity by optimizing doping ratio and/or increasing growth temperature, we used several liquid materials to support the fabrication process.…”
Section: Introductionmentioning
confidence: 99%
“…This precious control of mist flow, which makes mist CVD different from spray and AACVD techniques, is achieved by the following physics: the existence of Leidenfrost state droplets (ELSD) and the low probability of collisions between mist droplets (LPCD). 14–18 As reported in some of the literature, the 2 nd and 3 rd generation mist CVD has been used to fabricate several metal oxide films. 19–23…”
Section: Introductionmentioning
confidence: 99%
“…However, there are still issues regarding the controlling of surface morphology, growth direction and the cost [31][32][33]. It was reported that mist CVD had advantages on the film deposition such as high uniformity, high reproducibility, simplicity, easy to control, and low cost [34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%